“Estudio de maquinabilidad de aceros al carbono utilizando un fluido de corte biodegradable y natural” - Freire Loor, Luis Enrique (2020)
Biofuels currently represent a potential source of renewable energy. In addition, the last ones could be used to generate new and large markets for agricultural producers. However, only some of the current biofuel programs are viable and most of them involve both high social and ironically environmental costs. The economic, environmental, and social effects of biofuels must be widely discussed and be carefully evaluated before extending public sector support to large-scale biofuel programs. In this research project, an alternative of bio-lubricant (bio-fluid) for turning 1045 steel is experienced. An analysis of the main functions and influence of cutting fluids during metal machining is performed. An empirical mathematical model is obtained that allows to estimate the flank wear from the cutting speed and the machining time. According to the flank wear data obtained, these show that the bio-fluid is recommended for turning AISI 1045 steel in the range from 250 to 300 m/min.